Smoking is an independent risk factor for nosocomial sinusitis in neurocritical patients: evidence from a retrospective cohort study - Chen, Qiong; Zhang, Qindi; Wang, Dongmei; Yang, Man; Lai, Linyan; Cheng, Daihong; He, Ling; Liao, Xiaoyan (Frontiers in Neurology, 2025)
ObjectivesTo determine the risk factors associated with nosocomial sinusitis in general neurology ward patients with nasogastric tube (NGT) intubation and neurocritical care unit (NCU) patients.MethodsA retrospective cohort study was conducted in a tertiary hospital, Guangzhou, China. We enrolled two groups of patients: (1) general neurology ward patients with NGT intubation between July 2018 and March 2021, and (2) those admitted to NCU between January 2021 and December 2022. Eligible patients had at least two head MRI/CT scans with no baseline sinusitis. Nosocomial sinusitis was determined by senior physicians through imaging. Demographic and clinical data were collected from electronic medical records. Multivariate logistic regression was employed to analyze risk factors.ResultsIn total, 206 patients were included. Of these, 75 were from general neurology wards and 131 were from NCU. Nosocomial sinusitis occurred in 58.7% (44/75) of general neurology patients with NGT intubation and 59.5% (78/131) of NCU patients. Prior intubation of either ETT or NGT (odds ratio [OR] = 2.60, 95% Confidence Interval [CI] 1.15–5.88), prior intubation of both ETT and NGT (OR = 6.17, 95%CI 1.82–20.94), being a current smoker (OR = 2.53, 95%CI 1.29–4.96), and prolonged NCU stays (OR = 1.05, 95%CI 1.01–1.09) were risk factors for nosocomial sinusitis in the total samples. Specifically, prior intubation of both ETT and NGT (OR = 2.31, 95%CI 1.42–34.15), being a current smoker (OR = 3.47, 95%CI 1.45–8.29), and prolonged hospital stay (OR = 1.05, 95%CI 1.02–1.10) were risk factors for nosocomial sinusitis in NCU patients.ConclusionNosocomial sinusitis was prevalent among both general neurology ward patients with NGT intubation and NCU patients. Strategies, such as routine screening, promoting smoking cessation, and alternative enteral feeding methods, may help reduce the incidence of nosocomial sinusitis in this population.